(untitled) (Journal of the College of Basic Education, 2023)
This research is a continuation of a previous topic, during which we presented a detailed study on the spatial and temporal distribution of the population affected by the virus in Iraq from the start of the pandemic until the end of the world 2020, and because the virus is still affecting more and more, and this is shown through the continuation of cases of infections and deaths among the population, so we decided on this The research is to follow up on the development of cases of infection, recovery, and the number of deaths for the population under the influence of the virus throughout Iraq during the year 2021, with the aim of identifying an aspect of the health reality in Iraq and the measures taken by the Iraqi Ministry of Health to limit its spread.